The Bibliometric Mapping for Geospatial Intelligence in Remote Sensing-Based Maritime Weather Warning Systems: Bibliometric Mapping for Geospatial Intelligence in Remote Sensing-Based Maritime Weather Warning Systems - Sekar Dwianti, Fitri Anggraeni; Trismadi; Arief, Syachrul; Supriyadi, Asep Adang (UNIB Press, 2026)
The safety of shipping and the resilience of maritime infrastructure are affected by the accuracy of the early warning system against extreme weather. The use of Geospatial Intelligence (GEOINT) acts as an integrative framework that combines remote sensing data, spatial analysis, and the interpretation of geographic information for the increasing need for technology-based early detection in the face of increasingly complex marine climate dynamics, both for civilian and national defense interests. The purpose of this research is to analyze the development of global research over the past 25 years on this topic, as well as relate it to maritime infrastructure defense and resilience policies. The methodology used is bibliometric with a quantitative analysis approach to Scopus and Google Scholar publication data, as well as visualization using VOSviewer. The analysis includes the mapping of keyword trends, thematic clusters, institutional actors, and the evolution of research related to GEOINT, remote sensing, and maritime early warning systems. The results show significant improvements in the topic of satellite utilization (MODIS, Sentinel) and the integration of GEOINT big data and spatial analytics for early warning systems, but research on its application in the context of maritime defense policy is still limited. These findings provide strategic direction for the development of GEOINT as a data-driven policy support instrument that supports national shipping resilience and military preparedness in strategic maritime areas. The study also recommends a cross-sectoral research agenda that is more adaptive to the threat of extreme marine weather.